The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/molecules25184151
|View full text |Cite
|
Sign up to set email alerts
|

Effects of BDNF and PEC Nanoparticles on Osteocytes

Abstract: Bone substitute materials loaded with mediators that stimulate fracture healing are demanded in the clinical treatment in trauma surgery and orthopedics. Brain-derived neurotrophic factor (BDNF) enhances the proliferation and differentiation of mesenchymal stem cells into osteoblast. To load the implants with BDNF, a drug delivery system that allows the release of BDNF under spatiotemporal control would improve functionality. Polyelectrolyte complex nanoparticles (PECNP) have been reported as a suitable drug d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“… 49 BDNF is a growth factor described to play a role in the modulation of bone repair increasing the expression of the osteogenic markers. 50 IFN‐γ and IL‐1α are two important immunomodulators that trigger MSCs towards an anti‐inflammatory and pro‐trophic phenotype. 51 , 52 , 53 KLK3 is an angiogenesis suppressor.…”
Section: Discussionmentioning
confidence: 99%
“… 49 BDNF is a growth factor described to play a role in the modulation of bone repair increasing the expression of the osteogenic markers. 50 IFN‐γ and IL‐1α are two important immunomodulators that trigger MSCs towards an anti‐inflammatory and pro‐trophic phenotype. 51 , 52 , 53 KLK3 is an angiogenesis suppressor.…”
Section: Discussionmentioning
confidence: 99%
“…During the osteoblast differentiation and mineralization of bone marrow-derived stromal cells, these cells drive a program of gene expression governed by various transcription factors [ 33 ]. Runx2 is regarded as the master transcription factor that promotes the differentiation of mesenchymal progenitors into osteoblasts by regulating the expression of osteogenesis-related genes at the early stage of osteoblastic differentiation, such as ALP, collagen alpha 1 type I, and osteocalcin [ 31 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Limited by the difficulty of OCY extraction and culture technology, plenty of investigations showed that nearly all neurohormones had an effect on osteoblasts or osteoclasts (but not OCY) and exhibited bone anabolic or catabolic roles to regulate skeletal integrity; thus, the central control of OCY activity is almost blank ( 59 62 ). A recent study showed that the brain-derived neurotrophic factor, a growth factor mostly originated from the nervous system, plays a positive role on the proliferation of the murine osteocytic cell line MLO-Y4 ( 63 ). Co-injection of OCY into the brain exhibited tumor-suppressing capability through Lrp5, IL1ra, and β-catenin upregulation in brain metastases that occur from advanced breast cancer ( 25 ).…”
Section: Brain–ocy Crosstalkmentioning
confidence: 99%